Ionic mass transfer on fixed disk and conical electrodes under streaming solutions : I. Theoretical approach - Marchiano, Susana Lucy (1967)
A solution of the convective-diffusion differential equation for the case of disk and conical electrodes axially placed in laminar flow is attempted. The integration of the equations is done with an approximate streaming function which is valid for values of the function up to 0·3 within an error of one per cent. The rate equation for a steady convective-diffusion process on the disk electrode is [fórmula en el documento]. The type of solution is then extended to the case of conical electrodes with axial symmetry. A similar equation is thus obtained and the numerical coefficients for the average rate equation are in agreement with the one of the above equation, within 4 per cent, and are independent of the cone angle. The latter result agrees also with a previous equation deduced by analogy with the corresponding heat-transfer problem.